Residue Addition Can Mitigate Soil Health Challenges with Climate Change in Drylands: Insights from a Field Warming Experiment in Semi-Arid Texas - Pawan Devkota; Rakesh K. Singh; Nicholas G. Smith; Lindsey C. Slaughter; Natasja van Gestel (Soil Systems)
Texas cotton production is facing challenges from increased temperatures and extended droughts. We sought to determine whether applying a multi-species grass mulch on the surface of cotton fields in a semiarid region would mitigate some of the negative effects of climate change. We used open-top chambers (OTCs) to mimic climate warming and compared whether the effects of residue addition were similar between dryland and irrigated cotton fields located in the High Plains region of Texas during the summer of 2021. The OTCs raised the average air temperature by 2 °C. Under experimental warming, residue addition increased moisture content in non-irrigated (i.e., dryland) soils (+9.2%) and reduced the daily temperature range (by −1.4 °C) relative to uncovered soils. Furthermore, when pooled across irrigation and warming treatments, the addition of residue increased microbial biomass, soil respiration (+78.2%), and cotton yield (+15.2%) relative to uncovered soils. OTCs further enhanced the residue effects on microbial biomass by 34.9%. We also observed higher soil organic matter, microbial biomass, cotton biomass, and yield in irrigated fields compared to dryland, irrespective of residue addition. Our findings suggest that residue addition in dryland agriculture can mitigate the adverse effects of warming by stabilizing soil microclimates and promoting microbial growth and biomass by providing a more labile source of carbon, which, in turn, could boost the yield of cotton plants.